Where, if anywhere, did Rheita see Veronica's Veil?. (May 2017) - Covington, Michael A.
The asterism of Veronica's Veil reported by Rheita in 1645 is argued to be real, though inconspicuous; not a star cluster; and not correlated with Johannes Zahn's picture published in 1686 and widely redistributed. The asterism is most likely the rectangle bounded by ρ Leonis, β Sextantis, ο Leonis, and ι Hydrae, with some scattered interior stars interpreted as a face.